MAX WEBER’S RATIONALITY IN ACCOUNTING RESEARCH - Salah Uddin Rajib (Copernican Journal of Finance & Accounting, 2023)
Max Weber (1864–1920), a German political economist, sociologist and historian has been influencing the critical accounting research significantly since 20th century. This paper aims to investigate the influence of Weber’s ‘rationality’ concept in accounting research through the identification of research platforms, trends and major themes and findings. This study adopts the qualitative research methods. A number of papers from 1984 to 2021 have been analyzed to reach the aim. Call of modernization and human inheritance with tradition force men to act in a rational and calculative way which are the premise of Weber’s rationality. Through the three specific things – calculability, methodological behavior and reflexivity Weber defined rationality and its process in the society. The study finds that Weber’s rationality has been used to understand the society and its reflection in the implementation of accounting mechanisms. Various disciplines of accounting (financial accounting, management accounting and auditing) as well as implementation of various tools of accounting have been investigated under the concept of rationality. Both the public and private enterprises have been investigated under the concept of rationality. It is expected that the study will contribute to understand the application of Weber’s concept in accounting research and potentiality as well.